A Review of miRNAs as Biomarkers and Effect of Dietary Modulation in Obesity Associated Cognitive Decline and Neurodegenerative Disorders - Perdoncin, Maddie; Konrad, Alec; Wyner, Joshua R.; Lohana, Samir; Pillai, Sneha S.; Pereira, Duane G.; Lakhani, Hari Vishal; Sodhi, Komal (Frontiers in Molecular Neuroscience, 2021)
There has been a progressive increase in the prevalence of obesity and its comorbidities such as type 2 diabetes and cardiovascular diseases worldwide. Recent studies have suggested that the crosstalk between adipose tissue and central nervous system (CNS), through cellular mediators and signaling pathways, may causally link obesity with cognitive decline and give rise to neurodegenerative disorders. Several mechanisms have been proposed in obesity, including inflammation, oxidative stress, insulin resistance, altered lipid and cholesterol homeostasis, which may result in neuroinflammation, altered brain insulin signaling, amyloid-beta (Aβ) deposition and neuronal cell death. Since obesity is associated with functional and morphological alterations in the adipose tissues, the resulting peripheral immune response augments the development and progression of cognitive decline and increases susceptibility of neurodegenerative disorders, such as Alzheimer’s Disease (AD) and Parkinson’s Disease (PD). Studies have also elucidated an important role of high fat diet in the exacerbation of these clinical conditions. However, the underlying factors that propel and sustain this obesity associated cognitive decline and neurodegeneration, remains highly elusive. Moreover, the mechanisms linking these phenomena are not well-understood. The cumulative line of evidence have demonstrated an important role of microRNAs (miRNAs), a class of small non-coding RNAs that regulate gene expression and transcriptional changes, as biomarkers of pathophysiological conditions. Despite the lack of utility in current clinical practices, miRNAs have been shown to be highly specific and sensitive to the clinical condition being studied. Based on these observations, this review aims to assess the role of several miRNAs and aim to elucidate underlying mechanisms that link obesity with cognitive decline and neurodegenerative disorders. Furthermore, this review will also provide evidence for the effect of dietary modulation which can potentially ameliorate cognitive decline and neurodegenerative diseases associated with obesity.